Modernitas dan Pendidikan: Telisik Karakteristik Kurikulum Pendidikan Agama Islam di Madrasah - Afifah Salsa Bella; Muhammad Zuhdi; Bobi Erno Rusadi (Yayasan Al-Afif, 2025)
This study examines the characteristics of the Islamic Religious Education (PAI) curriculum implemented in madrasas. The PAI curriculum is designed to integrate religious and general learning in a balanced manner, with an emphasis on developing spiritual attitudes, knowledge, and skills consistent with Islamic values. The materials taught include the Qur'an, Hadith, Aqidah, Morals, Jurisprudence, and Islamic Cultural History, aiming to produce graduates who are faithful and have noble character. This curriculum is also designed to suit the needs of students and the socio-cultural context, while optimizing the role of teachers as learning facilitators. This study uses a literature review method with qualitative analysis based on documents and literature related to the PAI curriculum. The results indicate that the PAI curriculum in madrasas has advantages in integrating Islamic values into all aspects of learning, a comprehensive evaluation strategy, and strengthening madrasah management as an educational institution characterized by religion. This study provides a systematic overview of the characteristics of the PAI curriculum in madrasas as a reference for the development of effective and contextual religious education.